High genetic diversity despite drastic bottleneck in a critically endangered, long‐lived seabird, the Mascarene Petrel Pseudobulweria aterrima. (20th July 2020) - Lopez, Jade; Nikolic, Natacha; Riethmuller, Martin; Dubos, Jérôme; Pinet, Patrick; Souharce, Patxi; Couzi, François‐Xavier; Le Corre, Matthieu; Jaeger, Audrey; Humeau, Laurence
Abstract : The Mascarene Petrel Pseudobulweria aterrima is a critically endangered seabird endemic to Reunion Island, with an extremely small population suffering several threats. Fifteen polymorphic microsatellite loci were isolated from this species to analyse genetic diversity, estimate contemporary effective population size, search for evidence of a population bottleneck and see whether results support the hypothesis that life history traits could preserve allelic diversity in small populations. Results from 22 individuals found grounded as a consequence of light pollution highlight a surprisingly high genetic diversity, an absence of inbreeding, a contemporary effective population size estimated at approximately 1211 individuals and a probable bottleneck around 10 000 generations ago. Additional studies on genetic diversity and structure from a larger number of samples are thus required to evaluate the evolutionary potential of this critically endangered species.